Penanggulangan dampak Covid-19 bagi usaha mikro (studi pada implementasi Program Banpres Produktif melalui Peraturan Menteri Koperasi dan Usaha Kecil Menengah Nomor 6 Tahun 2020 di Kabupaten Lombok Timur) - Siti Hidayatul Jumaah; Dhea Candra Dewi; Fitriah Kartini; Novinaz Benita (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
This study aims to determine the implementation of the productive Banpres Program for Micro Business Actors during the Covid-19 pandemic, as well as to analyze the supporting and inhibiting factors of program implementation. This research is a descriptive study using a qualitative approach. In the process of collecting data, researchers used the methods of observation, interviews, and documentation. The results of the study indicate that the overall implementation of the productive Banpres program has been running effectively. This can be seen from the achievement of the variables in analyzing the implementation, namely (1) the communication variable indicates that the transmission, clarity, and consistency of the program has been running optimally, (2) the source variable indicates that human resources, information, authority, and supporting facilities have been fulfilled, (3) the attitude and disposition variables of the implementers show that cognition, direction, and response show optimal results, although the responses given by policy actors are not very solution-driven because of the limited authority given, and (4) the bureaucratic structure variable also shows results. optimal, because of the Standard Operating Procedure (SOP) in the implementation of the program. The supporting factors consist of a) rapidly developing technology so that it can be used as a means of support in communication and socialization, b) a high commitment from implementing actors, c) public support, and d) technical guidelines for the implementation of Banpres. Meanwhile, the inhibiting factors are: 1) the Banpres recipient community has low awareness in reporting the use of the budget, 2) not all micro-business actors who have proposed can be accepted as Banpres recipients, and 3) the authority to determine Banpres recipients is not delegated to the sub-district or village, making it difficult to monitor the use of the budget.